Efektivitas Cangkang Hama Bekicot (Achatina Fulica) Sebagai Adsorben Untuk Meningkatkan Kualitas Air Sungai Kahayan - Achmad Imam Santoso; Dhymas Sulistyono Putro (Fakultas Teknik, 2020)
The water quality of the Kahayan River is still below the criteria for clean water quality standards. One of the treatments to improve water quality is snail shells as adsorbents of heavy metals Fe and Zn are categorized as pests on fruit plants. The object of this research is the snail shell activated charcoal is used to improve the quality of river water on heavy metals Fe and Zn. The mass variation of snail shell activated charcoal weighing 0 grams, 5 grams, 10 grams, and 15 grams. The research process is divided into the Preparation Stage and Implementation Stage, where the implementation stage consists of making snail shell charcoal, making HCl solution, activating snail shell charcoal, and absorbing snail shell activated charcoal. Snail shell activated charcoal plays an active role in decreasing Fe and Zn concentrations. At 5 mg of snail shell activated charcoal was able to reduce 53% Fe concentration and 69% Zn concentration. Snail shell activated charcoal with a mass of 10 mg and 15 mg was able to reduce Fe concentration by 82% and 84%. Testing the Zn concentration in the mass of 10 mg and 15 mg was not read optically, due to the limited accuracy of laboratory equipment.